Implementasi Operasi Tangkap Tangan Yang Dilakukan Komisi Pemberantasan Korupsi - Muhammad Alfin Saputra (Universitas Islam Indonesia, 2020)
The purpose of this study is to examine the implementation of hand arrest operations (OTT) carried out by the Corruption Eradication Commission (KPK) and whether such operations go in line with the concept of hand arrest in the Indonesian Criminal Procedure Code (KUHAP). This is a normative research which is supported by information obtained from various sources, by utilizing statutory and conceptual approaches, analyzed in a qualitative descriptive method. The results of this study conclude that the hand arrest operation carried out by the Corruption Eradication Commission is in fact very effective in ensnaring the perpetrators of corruption crimes as it provides a cristal clear view on the criminal act that occurred in order to identify the suspect.